2013
DOI: 10.1148/radiol.12121385
|View full text |Cite
|
Sign up to set email alerts
|

Liver SULmeanat FDG PET/CT: Interreader Agreement and Impact of Placement of Volume of Interest

Abstract: Liver SUL(mean) at FDG PET/CT has excellent interreader agreement, with similar values and variance whether measured at the upper, lower, or portal vein levels within the right lobe of the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 21 publications
5
21
0
Order By: Relevance
“…The lowest variability of any of the studied organs was in the liver, where the COV was 13.8% for SUV mean and 14.5% for SUL mean , whereas the highest variability was in the spleen (38.7% with SUV mean and 38.8% for SUL mean ). For reference, the COV of the liver with 18 F-FDG PET has been reported to be 21.0%-23.1% using SUL mean (24). Only 1 of the 64 patients included in this study was imaged at more than a single time point, so no data are available on the relative roles of intrapatient (test-retest) versus interpatient variability.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest variability of any of the studied organs was in the liver, where the COV was 13.8% for SUV mean and 14.5% for SUL mean , whereas the highest variability was in the spleen (38.7% with SUV mean and 38.8% for SUL mean ). For reference, the COV of the liver with 18 F-FDG PET has been reported to be 21.0%-23.1% using SUL mean (24). Only 1 of the 64 patients included in this study was imaged at more than a single time point, so no data are available on the relative roles of intrapatient (test-retest) versus interpatient variability.…”
Section: Resultsmentioning
confidence: 99%
“…For the manual VOI 30 , according to our results and previous work from another group [23], the upper VOI was considered least variable between physicians. In order to simplify the analyses, we hereafter included it only into the analysis for (i) automated VOI 30 using 80-mm VOI medium , and (ii) manual VOI 30 placed at upper level.…”
Section: Resultsmentioning
confidence: 99%
“…A recent research report showed that VOI 30 placed in RL manually on the same FDG PET-CT study was reproducible between expert radiologists [23]. One may then argue that the automated method is not necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Liver SUV mean has also been utilized as normalization factor in PET derived quantitative therapy response formulations, which were further adapted to assess residual disease in colorectal malignancy [3,4]. In our previous work[5], we demonstrated that Liver SUL mean has almost perfect inter-reader reliability, regardless of whether the volume of interest (VOI) is placed at the upper, lower, or portal vein level of the right lobe of the liver and the inter reader variability is least in the upper aspect of the right lobe of the liver.…”
Section: Introductionmentioning
confidence: 99%